Two score and ten: my experiences in government - Ramakrishna, G. V. (New Delhi, 2004)
In this book, Ramakrishna provides a first hand account of how Government functioned at high levels in the States and at the Centre. The subtle methods of utilizing Government institutions for unconstitutional, political and bureaucratic ends have been brought out with modesty and sensitivity.
Keywords: Civil service-India